Beyond The Supererogatory: : Examining The Legal Discourse In A Motion For Clarification Vote - Vaneli Gaigher Marely, Alecio (Revista Científica Foz, 2026)
This study employs Critical Discourse Analysis (CDA) to examine a dissenting vote in a Brazilian Supreme Federal Court (STF) decision regarding the criminalization of homophobia. The research focuses on Minister Cristiano Zanin's arguments against extending the typification of homophobia to include racial insults. Using Fairclough's three-dimensional CDA model and incorporating Thompson's concepts of ideology and domination and Fiorin´s perspective of rhetorical arguments, this paper analyzes the linguistic strategies and power dynamics embedded in the legal discourse. The methodology involves a detailed examination of lexical choices, grammatical structures, and rhetorical devices in the dissenting vote. Key findings highlight the role of naturalization, reexamination, broadening and exceeding as discursive strategies employed in the vote.